(untitled) (Iranian Journal of Kidney Diseases, 2010)
Introduction. Despite many beneficial effects, hemodialysis may cause pulmonary dysfunction. On the other hand, patients with end-stage renal disease are potentially prone to lung edema and respiratory dysfunction. This study was conducted to evaluate the alterations of pulmonary function indicators after hemodialysis, measured by spirometry. Materials and Methods. A total of 26 patients on hemodialysis for at least 3 months were studied. They were all older than 18 years old. None of the patients was a current or recent smoker, and none of them had a history of respiratory diseases, current or recent respiratory infections, musculoskeletal disorders, or tuberculosis. All of the patients underwent the spirometry test before and after a 4-hour hemodialysis session, and the forced expiratory volume in the first second (FEV1), forced vital capacity (FVC), vital capacity (VC), and FEV1/FVC ratio were measured. Results. After hemodialysis, the FVC significantly increased (P = .02), while no significant improvement in the FEV1, VC, and FEV1/FVC ratio were observed. Gender was related to the changes in VC, with better results in women (P < .001). There was no association between the changes in spirometry parameters and age, body mass index, cause of kidney failure, type of anion used for hemodialysis, and weight changes. Conclusions. According to our results, pulmonary function, especially the FVC, improves after a session of hemodialysis.